HAART for children with treatment failure. Issue 5 (September 2009) - Sohn, Annette H; Ananworanich, Jintanat
Even as pediatric rollout programs are struggling to meet global need, increasing numbers of children are failing first-line antiretroviral therapy in low- and middle-income countries. Without better access to viral load monitoring, second-line antiretrovirals and research to guide optimal regimen selection, it will be difficult to ensure that HIV-infected children will survive into adulthood. Data available on pediatric drug resistance demonstrate that failure occurs early in childhood. Studies of salvage drug options have been promising, but are primarily conducted in adults. Evidence-based approaches to regimen selection, pediatric antiretroviral formulations and expanded access to novel drugs are now required to prepare for the future.